A saúde mental de estudantes de pós-graduação no contexto da pandemia da covid-19 : uma revisão de escopo - Souza, Breno Estevam Silva de (2024)
The COVID-19 pandemic had a significant impact on public health, resulting in substantial changes across various dimensions of society and influencing how people perceive the world. The social implications of the pandemic involve alterations in the daily lives of populations and implications for interpersonal relationships within families, schools, and workplaces. Accordingly, this study aims to identify and map scientific evidence regarding the mental health of graduate students (master's and doctoral) during the COVID-19 pandemic through a scoping review. This scoping review was developed in accordance with the guidelines of the Joanna Briggs Institute Manual and registered on the Open Science Framework (DOI: https://osf.io/jbem6). To formulate the research question, the PCC acronym (population, concept, and context) was used. Therefore, "population (P)" was defined as graduate students (master's and doctoral), while "concept (C)" was determined to be mental health, where we will address the psychopathologies that most affected this population. Finally, the "context (C)" was defined to encompass studies discussing mental health among graduate students during the COVID-19 pandemic, in order to answer the following question: "What are the scientific evidence related to the mental health of graduate students (master's and doctoral) during the COVID-19 pandemic?" Data collection was conducted in July 2023 from databases such as PubMed via MEDLINE, Web of Science, SciVerse Scopus (Elsevier), Embase, PsycINFO, LILACS via BVS, ProQuest Dissertations & Theses Global, and Google Scholar. For organizing the database generated during the review, we used the Rayyan software, which facilitated the removal of duplicates, followed by title and abstract screening and full-text reading, guided by the inclusion criteria defined in the protocol. A form containing basic information about the eligible studies was filled out, and all processes were conducted with software blinding activated and independently, as recommended by the JBI manual. The selection process and results presentation followed the PRISMA-ScR guidelines. The database search process resulted in 2,575 articles, of which 23 were selected for the review. The majority of studies were conducted in North America (United States 39.13%) and China (17.39%), totaling 56.52% of the studies. Most were published in 2022 and 2023, and the most frequent study designs were cross-sectional (91.3%). The studies mainly addressed the epidemiological profile (most frequent mental disorders) and associated factors, primary challenges faced by graduate students during the pandemic, self-care practices, and the use of health services. The key findings show an increase in the prevalence of mental disorders and associated factors during the COVID-19 pandemic. Psychological distress increased over the three phases of the COVID-19 pandemic, with varying degrees of increased anxiety and depression. The inability to continue academic work influenced increased anxiety and decreased motivation. Life satisfaction and happiness were positively associated with optimism about the future during the COVID-19 pandemic and negatively associated with depression and stress. It is concluded that the COVID-19 pandemic not only intensified preexisting challenges to the mental health of graduate students but also revealed the urgent need for adaptive and inclusive support strategies capable of meeting the diverse needs of this group during and beyond global crises.